2008
DOI: 10.1007/s11104-008-9786-y
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic toxicity to rice (Oryza sativa L.) in Bangladesh

Abstract: Natural contamination of groundwater with arsenic (As) occurs around the world but is most widespread in the river basin deltas of South and Southeast Asia. Shallow groundwater is extensively used in the Bengal basin for irrigation of rice in the dry winter season, leading to the possibility of As accumulation in soils, toxicity to rice and increased levels of As in rice grain and straw. The impact of As contaminated irrigation water on soilAs content and rice productivity was studied over two winter-season ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
129
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 269 publications
(159 citation statements)
references
References 28 publications
23
129
1
Order By: Relevance
“…At present, soybeans are grown in prime soils and also in marginal lands, where the occurrence of some As-contaminated soils has been documented for many years [16]. Bustingorri et al [13] found a negative correlation between soybean yields and soil As concentration, in agreement with similar studies in rice, wheat, and barley [7,17].…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…At present, soybeans are grown in prime soils and also in marginal lands, where the occurrence of some As-contaminated soils has been documented for many years [16]. Bustingorri et al [13] found a negative correlation between soybean yields and soil As concentration, in agreement with similar studies in rice, wheat, and barley [7,17].…”
Section: Introductionsupporting
confidence: 60%
“…Aerial biomass was less affected by As than roots in non-inoculated plants as described for rice, wheat [5,7,17], and soybeans [14]. Resembling the findings of other authors [26], inoculated plants were less affected by As.…”
Section: Resultsmentioning
confidence: 75%
“…The yield decline was associated with a decrease in the number of productive tillers. The authors note, also, that while arsenic concentrations in the rice grain were relatively high, ranging from 0.3 mg per kg to 0.6 mg per kg, concentrations in rice straw were much higher, ranging from about 2 mg per kg to 12 mg per kg [285].…”
Section: Extent Of the Problemmentioning
confidence: 93%
“…High arsenic concentrations can contribute to the development of straighthead disease, which can cause sterility after heading, in otherwise healthy rice plants [284]. Panaullah et al [285] observed a grain yield gradient on a rice field irrigated from a tubewell for 16 years in Bangladesh. During two crop seasons, grain yields declined from about 8000 kg per ha to 2500 kg per ha, as the concentration of total arsenic in the soil, across the field, increased from about 12 mg per kg to 70 mg per kg.…”
Section: Extent Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation